NIKAH MUHALLIL PERSPEKTIF EMPAT MADZHAB - Maryam Qurotul Aini, Siti; Ainiyah, Hilmi Huriyatul (JAS MERAH: Jurnal Hukum dan Ahwal al-Syakhsiyyah, 2022)
This article aims to reveal the views of the imams of the four schools of thought. The approach used is normative. Muhallil marriage is a marriage that is carried out to justify a person who has done triple talaq to immediately return to his wife with a new marriage. If a person has divorced his wife three times, either in one period or at different times, then the husband may no longer marry his ex-wife unless the wife has married another man, then divorces and her iddah expires. The purpose of marrying another man is not just doing a marriage contract, but having sexual relations as is the case for husband and wife life in general, then divorcing him properly so that the first husband can marry his ex-wife.